Structure and optical properties of anatase thin films produced by filtered cathodic vacuum arc method - Sakon Sansongsiri (2018)
© 2016, Hanyang University. All rights reserved. Titanium dioxide (TiO2) thin films were deposited on glass substrates by filtered cathodic vacuum arc system (lab-made) for various number of pulse modes at -50 VDC, and followed by 450°C annealing in air for 1 hr. The deposition pulses were 500 -2,000 pulses and the anatase film thickness was 13.0-37.5 nm. In this research, the roughness was increased with the increasing in the number of deposition pulses and film thickness. The transmission at 600 nm wavelength was 65-85%, decreasing with the film thickness, and the optical energy gap was in the range of 3.55-3.65 eV.